The ratio of serum Angiopoietin-1 to Angiopoietin-2 in patients with cervical cancer is a valuable diagnostic and prognostic biomarker - Ping Yang; Na Chen; Dongyun Yang; Janet Crane; Shouhua Yang; Hangyu Wang; Ruiqing Dong; Xiaoqing Yi; Lisha Xie; Guo Jing; Jing Cai; Zehua Wang (PeerJ, 2017)
Objectives Angiopoietins have been found to play essential roles in tumor angiogenesis. The present study was aimed at investigating the diagnostic and prognostic values of serum angiopoietin 1 and 2 (sAng-1 and sAng-2) in cervical cancer. Methods The sAng-1 and sAng-2 concentrations were analyzed in 77 women with cervical cancer, 44 women with cervical intraepithelial neoplasia (CIN) and 43 women without cervical lesions by enzyme-linked immunosorbent assay. The diagnostic values of sAng-1, sAng-2 and sAng-1/sAng-2 were evaluated by receiver operating characteristic (ROC) curves. The Ang-1 and Ang-2 expression in cervical cancer tissues as well as microvessel density (MVD), were assessed by immunohistochemistry. Results The concentration of sAng-2 gradually increased and the sAng-1/Ang-2 ratio was gradually decreased from normal control to CIN, then to squamous cell cancer, and the sAng-1/sAng-2 ratio was also significantly decreased in adenocarcinoma. The area under ROC curves of sAng-2 and sAng-1/sAng-2 ratio for discriminating cervical cancer from normal were 0.744 and 0.705, respectively. Decreased sAng-1/sAng-2 was significantly associated with advanced tumor stage, poor differentiation, lymph-vascular space invasion and high MVD. sAng-2 was positively correlated with the Ang-2 expression in cervix epithelia. A high sAng-1/sAng-2 ratio was associated with a longer progression-free survival and a longer overall survival in cervical cancer patients. Conclusions These findings suggest that sAng-2 and the sAng-1/sAng-2 ratio may be valuable diagnostic and prognostic biomarkers for cervical cancer.